Teaching Reading Using Zoom: Students’ Perception of Reading Class through Zoom - Rengganis Siwi Amumpuni; Rudi Hartono; Dwi Rukmini; Rahayu Puji Haryanti (International Conference on Science, Education, and Technology, 2022)
The pandemic has transformed instructional practices from face-to-face to online learning paradigms. Reading is one crucial skill for students. However, many students perceive reading as challenging to be learned. Teachers need to adapt to this transformation and investigate numerous online learning platforms. One of the famous and valuable platforms is Zoom It includes features such as a chat box, breakout rooms, and shared documents. In data collection, the researcher uses observation, documentation, and interview techniques. This descriptive qualitative research explores the students’ views of zoom in teaching reading. The result revealed that the advantages of zoom in teaching reading are the students become enthusiastic in the learning process, more excited and enjoy learning. Several good answer were gained from the learners as zoom facilitated live-online interaction and boosted their interest in an online course. The disadvantages are the problem with the internet quota and signal; some students don’t understand the material in detail and cheat when doing the assignment.